(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In this text we explored about some of the traditions in «Dede Gorgud» legends and between turkish society. We can indicate such an applause, curse, named, wedding, mourning traditions. In «Dede Gorgud» legends each traditions has own constant expressions and these formulas is repeated along the «Dede Gorgud» epics. It is known that the epos opens introduction in which the information on the legendary wise man and the storyteller Gorgud is supplied. In the epos there is no uniform plot. Each of twelve songs of legends is an independent narration. Ten legends are more closely connected among themselves and make, obviously, a uniform cycle of heroic feats the oguz athletes led by Bayundur-han. The white-bearded aged man Dede Gorgud, being an agsakkal tribe and the prophetic singer storyteller, is present at all the epos. He is the founder and the performer of legends in the epos, being thus and the participant of action. At the end of each legend of Gorgud composes the song in honor of the athlete, glorifies his feat and glorifies the khan to whom it is sung. Legends about Korkuda meet at all Turkic people of a kipchaksky and oguzsky branch: kazakh, turkmen, azerbaijanians, turks, also karakalpaks, gagauz, tatars, bashkir, etc.